Comparison of Short-term Effect of Video-assisted Thoracoscopic Surgery Lobectomy and Thoracotomy Lobectomy in the Treatment of Non-small cell Lung Cancer: A Systematic Review - Xuefei ZHANG; Xiaonan SHI; Biao HAN (Chinese Journal of Lung Cancer, 2012)
Background and objective Lung cancer is a common malignant tumor. The aim of this study is to assess the short-term effect of video-assisted thoracoscopic surgery lobectomy and thoracotomy lobectomy in the treatment of non-small cell lung cancer. Methods Cochrane Library, Embase, Pubmed, CBM, CNKI, VIP, and so on, were searched by computer. Randomized controlled trials comparing video-assisted thoracoscopic surgery lobectomy and thoracotomy lobectomy in the treatment of non-small cell lung cancer were collected. Two reviewers independently assessed the quality of included studies and extracted data. We analyzed the data using Review Manager (Version 5.0). Results Five randomized controlled trials totaling 537 patients were included. The results of meta analysis were as follows: statistically significant difference was found in operating time (SMD=0.27, 95%CI: 0.10–0.44), chest tube drainage flow (SMD=-0.23, 95%CI: -0.45–-0.01), postoperative hospital stay (SMD=-0.25, 95%CI: -0.46–-0.05), and postoperative complications (SMD=0.51, 95%CI: 0.32–0.80). No statistically significant difference was found in the harvested lymph nodes (SMD=-0.01, 95%CI: -0.22–0.19) between video-assisted thoracoscopic surgery lobectomy and thoracotomy lobectomy in the treatment of non-small cell lung cancer. Conclusion Compared with thoracotomy lobectomy in the treatment of non-small cell lung cancer, the amount of harvested lymph nodes was almost the same, but the amount of blood loss, operating time, chest tube drainage flow, and postoperative hospital stay were different.